Recurrent urinary tract infection as presenting feature of genito-urinary tuberculosis: reports of two cases (BIRDEM Medical Journal, 2020)
Genito-urinary tract is one of the most common extra-pulmonary sites of involvement by tuberculosis. Genitourinary tuberculosis poses significant diagnostic difficulty; not only because of non-specific symptoms, but also because of lack of diagnostic facility, specially, in resource constrain settings. We report two cases of genito-urinary tuberculosis occurring among Bangladeshi adult females, who presented with recurrent urinary tract infection. Along with other supportive tests, acid fast bacilli were identified on urine examinations.Birdem Med J 2020; 10(3): 212-214